2010
DOI: 10.1080/07391102.2010.10507336
|View full text |Cite
|
Sign up to set email alerts
|

In SilicoStructural and Functional Analysis of Fragments of the Ankyrin Repeat Protein p18INK4c

Abstract: Ankyrin repeat proteins (ARPs) are ubiquitous proteins that play critical regulatory roles in organisms and consist of repeating motifs (ankyrin repeats) stacked in non-globular, almost linear, "quasi one-dimensional" configurations. They also have highly unusual mechanical properties, notably ARPs can behave as nano-springs. Both their essential cellular functions and distinctive nano-mechanical properties have aroused interest in ARPs for potential applications in medicine and nanotechnology. Further, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 73 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Evolutionary relationships between different groups of pectin lyase proteins could not be inferred. By contrast, within each group, strong amino acid sequence and gene organization conservation were evident, suggesting strong evolutionary relationships among subfamily members [24], [25], [26]. Phylogenetic analyses also showed that several pairs of pectin lyase proteins were putative paralogs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Evolutionary relationships between different groups of pectin lyase proteins could not be inferred. By contrast, within each group, strong amino acid sequence and gene organization conservation were evident, suggesting strong evolutionary relationships among subfamily members [24], [25], [26]. Phylogenetic analyses also showed that several pairs of pectin lyase proteins were putative paralogs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…All MD simulations were carried out using the AMBER suite of programs with the all-atomic force fields ff99, ff99SB, and ff03 . The simulation protocol, which has been repeatedly shown to perform well for proteins, was set up as follows. The hydrogen atoms were added by the LEaP module of AMBER.…”
Section: Methodsmentioning
confidence: 99%
“…The statistical result of the lack of preferential interactions between amino acids is based on a large number of already folded protein structures, and therefore it is safe to interpret it as the consequence rather than the cause of protein folding. However, it must be noted that the preferential interactions between amino acids are the basis of the development of knowledge-based potentials, which in turn form the underpinning of protein structure prediction by modeling and simulation (Ji & Liu, 2011a;Rackovsky & Schraga, 2011;Sarma, 2011) that are now routinely performed in many laboratories across the globe (Aman et al, 2010;Sklenovský & Otyepka, 2010;Tao et al, 2010). The lack of preferential interactions between amino acids in a large sample set suggests that the nonpreferential or random inter-residue interactions might maintain the structural stability of the already folded proteins.…”
Section: Stoichiometry-driven Protein Folding Hypothesismentioning
confidence: 99%